(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
Sintok and Cilik islands of Karimunjawa are located in an area with potentials for SCUBA diving and snorkeling tourism. While these areas are developed into tourist destinations, efforts to preserve the environment need to be carried out. As a consequence, assessment of diving and snorkeling tourism management needs to be conducted by referring to indicators pertaining to the environmental aspects specified by the United Nations World Tourism Organization (UNWTO). The carrying capacity of the diving and snorkeling tourism sites needs to be measured so that the area can be a sustainable tourism destination. The objective of the study is to conduct an assessment of environmental aspects as an effort in implementing sustainable tourism development. Another objective is to identify the Tourism Suitability Index (TSI) and carrying capacity of the SCUBA diving and snorkeling tourism sites in Sintok and Cilik islands. The research methods employed were in-depth interviews and field observations. Study results indicate that Sintok island and Cilik island scored 23 and 24, respectively, for the environmental aspects in sustainable tourism development, with an average value of 3 for both islands. Based on these scores, they are categorized as “fairly suitable” with sustainable tourism development. The TSI scores obtained for SCUBA diving and snorkeling tourism in Sintok and Cilik islands are categorized as “highly suitable” (S1) and “fairly suitable” (S2). The tourism area’s carrying capacity of the SCUBA diving and snorkeling tourism sites in Sintok island is 2,406 persons/day, while Cilik island’s carrying capacity is 510 persons/day.